STUDI LITERATUR IMPLEMENTASI DIGITALISASI KEBIJAKAN PUBLIK DI TINGKAT PEMERINTAH KOTA DI INDONESIA - Fernando Marpaung; Dahyar Daraba; Ruth Roselin Erniwaty Nainggolan (Fakultas Politik Pemerintahan IPDN, 2026)
Abstract Government digitalization has become one of the key strategies in improving the quality of public services and governance in Indonesia. Municipal governments, as the frontline of public service delivery, play a strategic role in implementing digital policies, particularly through the development of e-government and smart city initiatives. This study aims to analyze the implementation of public policy digitalization at the municipal government level in Indonesia, including its forms and models of implementation, supporting and inhibiting factors, as well as its impact on public services. This research employs a qualitative approach using a literature review method, drawing on various scientific sources and relevant policy documents. The findings indicate that the implementation of digitalization in municipal governments has developed rapidly, as evidenced by the increasing adoption of digital-based services such as online licensing, population administration, and public complaint systems. However, such implementation is still predominantly sectoral and not yet fully integrated. The main supporting factors include infrastructure readiness, human resource capacity, institutional support, and visionary leadership. On the other hand, the challenges faced include system fragmentation, low interoperability, limited human resources, and the digital divide within society. Digitalization has contributed positively to improving efficiency, transparency, service accessibility, and public participation. Nevertheless, without proper management, digitalization also has the potential to create social exclusion and unequal access to services. Therefore, a more comprehensive and integrated approach is required in developing digital policies, one that not only focuses on technology but also emphasizes institutional strengthening and social inclusiveness. Keywords: government digitalization, e-government, public policy, municipal government